Isolation and nucleotide sequence survey of the ribosomal protein gene (RPL27) from human nasopharyngeal-derived cell lines - Buwaneswari, Nagayan (Universiti Malaysia Sarawak, UNIMAS, 2012)
This study is about isolation and nucleotide sequence survey of RPL27 gene in human nasopharyngeal cell line. Literature has been stated that RPL27 gene found to be downregulated in nasopharyngeal carcinoma cases. The ribosomal protein L27 gene has been used in expression studies of human nasopharyngeal carcinoma but there is no studies related to the nucleotide sequence analysis of RPL27 gene in nasopharyngeal carcinoma cases. Moreover, most of the studies that have been conducted using this gene are using tissue rather than cell line as sample. The main aim of the study is to isolate and study the nucleotide sequence of RPL27 gene from human nasopharyngeal carcinoma and normal cell line. The methods used in this study are isolation of total RNA using TRIzol method, reverse transcriptase polymerase chain reaction, and amplification of DNA, purifying, sequencing and finally analyzing the nucleotide sequence of the RPL27 gene using bioinformatics. From this study, it can be found that, there is no nucleotide variation occurs due to mutation in the region of study in RPL27 gene derived from both nasopharyngeal normal and carcinoma cell line.